2014
DOI: 10.2134/agronj13.0565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relay Cropping of Corn on the Productivity and Quality of Flue‐Cured Tobacco

Abstract: Relay cropping timing has been frequently reported to in uence ue-cured tobacco (Nicotiana tabacum L.) production. However, the optimal planting time for a relay corn (Zea mays L.) crop on ue-cured tobacco elds is unknown in terms of tobacco health, yield, quality, and economic value. A eld experiment was conducted with 10, 17, 24, and 31 d a er ue-cured tobacco apex excision as the relay cropping timings of corn, and tobacco monoculture as the control at Chuxiong, Yunnan, China in 2010 and 2011. e ve treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…As the biggest country to produce and consume tobacco in the world, tobacco industry plays vital role in China's economy . However, continuous cropping of tobacco in the same farmland would shift the diversity distribution of microbial community in tobacco soil and decrease the yield and quality of tobacco leaves . It was reported that phenolic acids in soil were one of the important compounds to induce this phenomenon of continuous cropping obstacle in crop planting .…”
Section: Introductionmentioning
confidence: 99%
“…As the biggest country to produce and consume tobacco in the world, tobacco industry plays vital role in China's economy . However, continuous cropping of tobacco in the same farmland would shift the diversity distribution of microbial community in tobacco soil and decrease the yield and quality of tobacco leaves . It was reported that phenolic acids in soil were one of the important compounds to induce this phenomenon of continuous cropping obstacle in crop planting .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study demonstrate that the flue‐cured tobacco and corn relay‐intercropping system was much more profitable than monoculture corn because the relay‐intercropping system can grow a highly profitable flue‐cured tobacco crop in addition to the relay‐intercrop corn and, thus, increased the economic returns from the land to farmers. On the other hand, the findings about the effects of relay‐intercropped corn on flue‐cured tobacco (Zhou et al, 2014) demonstrated that the flue‐cured tobacco and corn relay‐intercropping system when corn was intercropped at earlier dates was more profitable than monoculture flue‐cured tobacco because relay intercropping of corn at earlier dates did not negatively affect flue‐cured tobacco yield or economic value but produced a profitable relay‐intercropped corn crop. Compared with the net return of monoculture flue‐cure tobacco of $7465.00 ha −1 in this study (Zhou et al, 2014), the whole system net return when corn was intercropped 10 and 17 d after flue‐cured tobacco apex excision was $376.70 ha −1 and $129.00 ha −1 higher, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the findings about the effects of relay‐intercropped corn on flue‐cured tobacco (Zhou et al, 2014) demonstrated that the flue‐cured tobacco and corn relay‐intercropping system when corn was intercropped at earlier dates was more profitable than monoculture flue‐cured tobacco because relay intercropping of corn at earlier dates did not negatively affect flue‐cured tobacco yield or economic value but produced a profitable relay‐intercropped corn crop. Compared with the net return of monoculture flue‐cure tobacco of $7465.00 ha −1 in this study (Zhou et al, 2014), the whole system net return when corn was intercropped 10 and 17 d after flue‐cured tobacco apex excision was $376.70 ha −1 and $129.00 ha −1 higher, respectively. In contrast, the whole system net return when corn was intercropped 24 and 31 d after flue‐cured tobacco apex excision was $360.30 ha −1 and $224.80 ha −1 lower than the net return of monoculture flue‐cured tobacco, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations